Potensi Lecanicillium lecanii untuk Pengendalian Helopeltis antonii pada Tanaman Teh - Gusti Indriati; Samsudin Samsudin; Widi Amaria (Jurnal Tanaman Industri dan Penyegar, 2015)
Lecanicillium lecanii is an entomopathogenic fungus that potential to control tea mosquito bug Helopeltis antonii. The research aimed to determine the potential of L. lecanii in controlling H. antonii in tea plant. The research was conducted at the Laboratory of Plant Protection, Indonesian Industrial and Beverages Crops Research Institute (IIBCRI) Sukabumi, from January to October 2014. The study consisted of infectivity and antifeedancy of L. lecanii on H. antonii nymph, as well as its in vitro compatibility with botanical insecticide, using completely randomized design (CRD). The infectivity and antifeedancy tests of L. lecanii on H. antonii nymph were carried out using 4 densities: 106, 107, 108, 109 conidia/ml, and control. Each treatment of infectivity test was repeated 4 times with observed variables were mortality and development of nymphs. Meanwhile, antifeedancy test was repeated 10 times with the observed variable was percentage of feeding reduction. The in vitro compatibility test of L. lecanii was done by using Piper retrofractum (PR), Tephrosia vogelii (TV) and Annona squamosa (AS) powder with the concentration of 2.5%, 5.0%, 7.5%, respectively and control, which repeated 4 times. The results showed that L. lecanii capable to infect and kill H. antonii nymph at about 65% in laboratory and reduce feeding about 83.04%. Addition of A. squamosa and T. vogelii powder at 2.5%–7.5% concentration were not significantly affecting the growth of L. lecanii colonies on PDA media. On the other hand, addition of P. retrofractum powder with the same concentration was considerably inhibiting the growth of L. lecanii. This result demonstrates that A. squamosa and T. vogelii powder are compatible with L. lecanii.